Educating school students and gauging their perception about the harmful effects of smoking using a "Facial-Ageing App (mobile application):"An experience from Malaysia - Roy Rillera Marzo; Sudip Bhattacharya; Shalini Ravichandran; Pavithra Lakshmanan; Valerie Rukshana Jeffery; Praveena Moralitheran; Amaluddin Ahmad; Jegathambigai Ramashwar Naidu (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Smoking is one of the leading factors of mortality in Malaysia. Most youngsters start at adolescence, fascinated by the concept of smoking. Interventions that harness the broad availability of mobile phones, as well as adolescents' interest in their appearance, may be an innovative way to advance school-based prevention. This study aims to determine the perceptions of facial-aging apps among secondary school students. METHODOLOGY: For this research, descriptive cross-sectional study using simple random sampling method was used. Population sampling was targeted toward three government schools. The total number of respondents is 383, with all of them aged between 13 and- 16 years of age. Legal considerations were taken to maintain the confidentiality of respondents. The specific objectives are: 1. To determine the level of change of intention on smoking, 2. To know the perceived reactions of the peer groups on the appearances of students as nonsmokers, 3. To determine whether the students learned new benefits of nonsmokingand, 4. To measure the impact of a facial-aging app among students. RESULTS: The number of respondents who smoke was 40 (10.4%), while the number of respondents who do not smoke was 343 (89.6%). About 89% of the respondents agree that their three-dimensional selfie image motivates them not to smoke. In addition, 87.8% of respondents admit that the perceived reactions of their classmates make them think that they look better as nonsmokers. After learning the effects of smoking, about 86.4% of the respondents acknowledged that they would educate their peer groups. Furthermore, 85.9% of the respondents found this "Smokerface" app enjoyable. CONCLUSION: The facial-aging intervention was effective in motivating Malaysian pupils to stay away from tobacco use. Thus, the analysis on the study of facial app usage in smoking prevention among youngsters concludes that most of the adolescents concur that the "Smokerface" app helps in the prevention of smoking among youths.